An Internet Based Intervention for Adults With Autism Spectrum Disorder—A Qualitative Study of Participants Experiences - Westerberg, Britta; Bäärnhielm, Sofie; Giles, Clover; Hylén, Ulrika; Holländare, Fredrik; Bejerot, Susanne (Frontiers in Psychiatry, 2021)
Background: Adults with Autism Spectrum Disorder face several barriers to accessing evidence-based care, including difficulties in communicating needs, social anxiety or in travelling to a health care unit. In recent years, several forms of internet-based treatments have shown to be effective for a variety of psychiatric conditions. Internet-based treatment alternatives allow convenient and flexible formats, and therefore have the potential to increase access to health care for individuals with autism spectrum disorder. However, knowledge about how internet-based treatment features may suit the needs of individuals with autism is limited. The aim of this study was to explore the participant experiences of an internet-based intervention for adults with autism spectrum disorder. The primary focus of the investigation was on autism-specific needs in relation to the features unique to the online format. Methods: In this qualitative study, semi-structured telephone interviews were conducted with fourteen participants who had completed a text-based internet-based intervention for adults with autism spectrum disorder. We used an inductive approach and analysed the data using qualitative content analysis. Results: Five main categories were identified; (1) Implications of the online format, (2) The fixed non-individualized model, (3) Therapist interaction, (4) Interacting with other participants and (5) Making use of the treatment content. Overall, participants appreciated the availability and that they could work on their treatment independent of time or location. Among those participating in group-based chat-sessions with the other participants, it was considered a generally positive experience. Furthermore, most participants felt safe and relaxed in relation to the therapist and appreciated the text-based format. However, several participants felt that the format and content of the treatment was not sufficiently adapted to their individual life situation. Conclusion: In conclusion, this internet-based treatment constitutes an accessible and energy-saving treatment alternative for adults with autism. Further, integrating group-based components seems feasible in an otherwise individual internet-based treatment for individuals with autism. However, group-based components do require a clear purpose and rationale. Future studies should develop and evaluate treatment adaptations tailored to individual needs.